VD_FINDINFO Faillite / 2016 / 3 vom 18. Januar 2016 - VD Tribunal cantonal (2016)
OUVERTURE DE LA FAILLITE, DÉLAI DE RECOURS, FICTION DE LA NOTIFICATION, NOTIFICATION IRRÉGULIÈRE | 168 LP, 174 al. 1 LP, 174 al. 2 LP, 174 LP, 138 al. 1 CPC (CH), 138 al. 3 let. a CPC (CH)